Avaliação das ações de inclusão digital implementadas pela UFC no contexto da pandemia de Covid-19 (2020 – 2021) com foco nos discentes em situação de vulnerabilidade social - Brito, Raquel Maria Gois (2024)
In recent decades, new technological tools have transformed the various levels of human society's interaction, revolutionizing everything from the way we carry out activities related to basic and essential human survival to the way we work, educate, and entertain ourselves. In this scenario, the public policy of digital inclusion in the Brazilian context emerges as a means to ensure access to modern communication, work, and educational technologies for a portion of the population that, due to socio-economic differences, sometimes of historical nature, remains excluded from the so-called digital society, unable to exercise their fundamental rights in the emerging social, economic, and cultural landscape. Furthermore, with the advent of the COVID-19 pandemic, especially in the period from 2020 to 2021, the need for participation in the digital realm, as well as the use and mastery of contemporary information technologies, became even more essential as in-person activities were suspended for long periods. The digital medium became the only viable means for carrying out activities without the risk of potential virus transmission, particularly in the academic sphere. In this context, the Federal University of Ceará (UFC), during the mentioned period, conceived and implemented a series of actions with the aim of facilitating digital inclusion for socially vulnerable students through the Emergency Pedagogical Plan (PPE) and its related initiatives, aiming to ensure the fundamental right to education for the academic community subject to these actions. Thus, this work seeks to evaluate these actions, both quantitatively and qualitatively, emphasizing the multiple elements that make up the highlighted quali-quantitative study, as well as the parameters for the proposed qualitative evaluation, with an emphasis on Raul Lejano's post-constructivist approach (2012) and the evaluative perspective of digital inclusion that permeates Mark Warschauer's work (2006). From the results obtained from the bibliographic research, questionnaires, and interviews conducted with the benefited students, as well as with the teachers, administrators, and public servants involved in the development of inclusive actions, it was possible to perceive more accurately the context of the public policy in question. It was also concluded that merely providing equipment and internet access is not enough to achieve adequate digital inclusion. It is essential to reduce social inequalities as a tool to reach this goal. Furthermore, during the study, an analysis will be made of the close relationship between Brazilian social and economic inequality and the phenomenon of digital exclusion. It will also detail the evolution of public policy for digital inclusion in Brazil, highlighting the main phases outlined in academic literature, as well as the key aspects and actions that stood out in each stage of improving national inclusive efforts.